New Headway : Beginner Workbook Without Key - Soars, Liz and Soars, John (Oxford, New York Oxford University Press, 2014)
A foundation course in basic English for zero-English beginners
Include Illustration
Keywords: English language -- English language--Study and teaching--Foreign speakers -- English language--Spoken English--Study and teaching